Dokunmamış kumaş esaslı fonsiyonel kompozit panel tasarımı - Beyit, Ali (My University, 2023)
Bu çalışmada, farklı hammadde kaynaklarının kullanıldığı dokunmamış kumaş katmanlarının bir araya getirilmesi şeklinde tasarlanan çok fonksiyonlu kompozit panel geliştirilmiştir. Üretilen paneller, ses yutum, mukavemet, elektromanyetik kalkanlama etkinliği (EMSE), güç tutuşurluk, yanmazlık ve kumaş yapılarının ısı yalıtım özellikleri açısından değerlendirilmiştir. Panel katmanlarının üretiminde, tülbent doku oluşturma aşamasında, tarak makinesi ve doku bağlama aşamasında iğneleme makinası kullanılmıştır. Bağlayıcı olarak kullanılan iki bileşenli iç/ dış (PET/ CO-PET) kesikli Poliester elyafı tüm katmanlarda sabit %25 oranında tutulmuştur. Kompozit katmanlarından biri olan dokunmamış kumaşta en uygun maliyet ve özellikte elektromanyetik kalkanlama özelliğini sağlamak amacıyla çelik elyaf %1, %2,5, %5, %7,5, %10, %12,5, %15, %17,5, %20, %22,5, %25, %27,5 ve %30 oranlarında kullanılarak dokunmamış kumaşlar üretilmiştir. Yapılan testler sonucunda %20 çelik elyaf içeren dokunmamış kumaşlarda hem maliyet hem de istenen özellik bakımından en uygun değerler elde edilmiştir. %20 paslanmaz çelik elyaf kullanılarak üretilen dokunmamış kumaşın, 1800MHz frekansında 15dB ile genel kullanımda en az %90 elektromanyetik kalkanlama değerine sahip olduğu bulunmuştur. Fonksiyonel kompozit panel üretimi için 8 katmanlı dokunmamış kumaşlar bir araya getirilmiştir. 8 katmandan oluşan panelin içersindeki ilk çift katmanında ses yutum özelliği için %75 Poliamid ve pamuk elyafı içeren çorap atıkları ve %25 İki bileşenli kesikli bağlayıcı Poliester elyaf kullanılmıştır. İç katmanın üzerine elektromanyetik kalkanlama özelliği için en uygun değer olarak belirlenen %20 çelik elyafı, %55 geri dönüşüm-PES ve %25 İki bileşenli kesikli bağlayıcı Poliester elyaftan ikinci katman eklenmiştir. Üçüncü katmanda ısı yalıtımı özelliği için %75 kenevir elyafı ve %25 İki bileşenli iç/ dış bağlayıcı kesikli Poliester elyaf kullanılmıştır. Dördüncü katman olan en dış katmanda güç tutuşur özelliğe sahip %75 güç tutuşur PES elyaf ve %25 İki bileşenli Poliester elyaf kullanılmıştır. Dokunmamış kumaş esaslı fonksiyonel kompozit paneller sıcak pres makinesi kullanılarak 3mm, 5mm, 10mm ve 15 mm olmak üzere 4 farklı kalınlıkta üretilmiş, P1 (3 mm), P2 (5 mm), P3 (10 mm) ve P4 (15 mm) olarak kodlanmıştır. Üretilen panellere mukavemet, ses yutum, ısı yalıtım, elektro manyetik kalkanlama ve güş tutuşurluk testleri uygulanmıştır. Farklı kalınlıkta üretilen panellerin elastiklik modülü (E), maksimum gerilme kuvveti (M), maksimum kuvvetteki %uzama miktarı (εTm), kopma mukavemeti (B) ve kopma uzama değeri (εB) ölçülerek değerlendirilmiştir. Sonuçlar, kopma mukavemetinin ve kopma uzamasının değişimlerinin fonksiyonel kompozit panellerin kalınlığına bağlı olarak düşüş gösterdiği tespit edilmiştir. Öyle ki, kopma mukavemeti değeri P1 kodlu 3mm kalınlıkta üretilen panelde 5.42MPa iken, P4 kodlu 15mm kalınlıkta üretilen panelde 0.56MPa olarak tespit edilmiştir. Fonksiyonel kompozit panellerin Limit Oksijen değerleri (LOI) 24 ile 28 arasında bulunmuştur. P1 ve P2 kodlu panellerin LOI değeri 28’e ulaşmıştır. En yüksek ses yutum katsayısı, kalınlığı 15mm olan panel ve en düşük ses yutum katsayısı, kalınlığı 3mm olan panelde elde edilmiştir. Panellerin ses yutum performansları 16-315Hz frekans aralığında düşük seviyede kalmaktadır. Panellerin ses yutum performansları 315-6300Hz frekans aralığında yüksek seviyeye erişmiştir. Dört farklı kalınlıkta üretilen panellerde 0.1-3GHz frekans aralığında yapılan EMSE testlerinde, panellerin elektromanyetik dalgaların %99’luk kısmını absorbe ettiği ve geri kalan %1 kısmını ise geri yansıttığı tespit edilmiştir. Dokunmamış kumaş esaslı katmanlarıni panel formuna dönüştürülmesi ile birlikte müthiş bir performans yükselmesi olduğu görülmüştür. Test sonuçları, geliştirilmiş fonksiyonel kompozit panellerin katmanlarında farklı lifler kullanılarak üretilen dokunmamış kumaşların, pres işlemi ile birleştirildiğinde üstün işlevlere sahip olduğunu göstermektedir.

In this project, a multifunctional panel by combining non-woven fabric layers produced from several raw material sources was developed. The properties of sound absorption, tensile strength, electromagnetic shielding effectiveness (EMSE), flame-retardant characteristics, combustion behaviour and thermal insulation of the all produced multifunctional panels were tested and measured. The laboratory type carding machine for web forming and the needle punching machine for web bonding in the production of nonwoven fabrics that form the layers of multifunctional panels were used. Bi-component sheath/ core type binder polyester (PET/ co-PET) staple fibre for each layers of multifunctional panels was only used at the ratio of 25%. The carded and needle punched nonwoven fabrics from staple stainless steel fibres in the ratio of 1%, 2,5%, 5%, 7,5%, 10%, 15%, 17,5%, 20%, 22,5%, 25%, 27,5% and 30% were manufactured for providing optimum electromagnetic shielding effectiveness values in the terms of cost and desired fabric properties in the nonwoven fabric that forms one of the layers of the multifunctional panel. After test studies, the optimum shielding values at the nonwoven fabric with 20% stainless steel fibre in terms of cost and desired properties were obtained. It has been noticed that the nonwoven fabric with 20% stainless steel fibre has obtained 15dB EMSE value in the frequency range of 1800MHz and 90% shielding protection percentage in the general use. The four different and eight layers of nonwoven fabrics were combined for multifunctional composite panel production. The needle punched nonwoven fabric with 75% polyamide/ cotton and 25% bi-component polyester binder staple fibre for sound absorption were used in the innermost double layer of the multifunctional composite panel consisting of eight nonwoven fabric layers. The nonwoven fabric with 20% stainless steel fibre, %55 recycled polyester and 25% bi-component polyester binder staple fibre, which was proven to be the most appropriate value for electromagnetic shielding, were put on the nonwoven fabric in the innermost layer of multifunctional composite panel. The nonwoven fabric with 75% hemp fibre and 25% bi-component polyester binder staple fibre for thermal insulation in the third layer of the multifunctional panel were used. The nonwoven fabric with 75% flame retardant polyester fibre and 25% bi-component polyester binder staple fibre at the outermost and fourth layer of the multifunctional panel were preferred. The multifunctional composite panels consisting of carded and needle-punched nonwoven fabrics were manufactured by using hot pressing method at four different thickness as 3mm, 5mm, 10mm and 15mm. The multifunctional panels were coded as P1 (3mm), P2 (5mm), P3 (10mm) and P4 (15mm). The properties of tensile strength, sound absorption, thermal insulation, electromagnetic shielding effectiveness, flame retardance and combustion behaviour produced multifunctional composite panels were tested. The multifunctional composite panels produced at different thickness values were measured and evaluated in terms of elastic modulus (Et), maximum tensile strength (M), maximum % elongation (εTm), breaking strength (B), and total % elongation at break (εB). The obtained results showed that the breaking strength and total % elongation values at break were decreased depending on the thickness of the multifunctional composite panels. While the breaking strength value of multifunctional composite panel having 3mm and with P1 code was 5.42MPa, multifunctional panel having 15mm thickness with P4 code was only found as 0.56MPa. Limit Oxygen Index (LOI) values of multifunctional composite panels were found between 24 and 289. The LOI values of multifunctional composite panels with P1 and P2 code were reached to 28. The highest sound absorption coefficient in the all multifunctional ccomposite panels was found at panel with P4 code. On the other hand, the lowest sound absorption coefficient was seen at panel with P1 (3mm). It was seen that the performance of sound absorption of the multifunctional composite panels was the lowest value in the frequencies ranging from 16Hz and 315Hz. The performance of sound absorption of the multifunctional composite panels has reached to excellent level in the frequencies ranging from 315Hz and 6300 Hz. It can be highlighted that the panels developed at four (four) different thicknesses absorb 99% of the electromagnetic waves in the frequencies ranging from 0.1-3GHz frequency band and reflect the remaining 1%. It has been revealed that converting it to panel form results in a significant gain in performance. The test results clearly showed that when the nonwoven fabrics were hot-pressed into multifunctional composite panels, the multifunctional panels have outstanding properties.
Design of multifunctional composite panel based on nonwoven fabric
Keywords: Composite panel; conductive stainless steel fiber; Construction industry; Construction technical textiles; Dokunmamış kumaş; Electromagnetic shielding; Elektromanyetik kalkanlama; flame retardant; flame retardant fiber; geri kazanılmış poliester elyaf; güç tutuşur elyaf Nonwoven fabric; güç tutuşurluk; hemp fiber; Insulation (Heat); ısı yalıtımı; iletken çelik elyaf; İnşaat teknik tekstilleri; kenevir elyaf; Kompozit panel; Malzemeler; Materials; recycled polyester fiber; ses yalıtımı; sound insulation; Tekstil endüstrisi; Textile industry; thermal insulation; Yalıtım (Isı); Yapı endüstrisi